Czeska i słowacka tradycja międzyliterackości w kontekście współczesnej komparatystyki (założenia i źródła ideowe chrestomatii "Koncepcja międzyliterackości w literaturoznawstwie porównawczym") - Zelenka, Miloš (Wydawnictwo-Drukarnia Bonami/Pracownia Komparatystyki Literackiej IFP UAM, 2007)
The author presents a selection of theoretical works on comparative literature and cultural studies. The anthology entitled The concept of interliterariness in comparative literature will unite the diachronic survey of the changes undergoing in comparative studies and present the diversity of the contemporary schools and initiatives. The anthology project, that encapsulates the whole 20th century, contains scientific concepts organised according to their approach towards the issue of interliterariness. It is exactly the feature of interliterariness that is exhibited as substantial for modern comparative studies. The anthology includes works of, i.a. P. van Tieghem, D. Ďurišin, M. Žyrmunski, J. Lotman, R. Wellek, S. Bassnet, M. Bakoš, representatives of postcolonial studies, cultural theories of literariness and others. The largest part of the anthology is occupied by research organised into the following units: genealogy, emigrantology, thematology, imagology, feminist studies, literary translation and criticism, eurocentrism studies. The anthology project prepared by M. Zelenka together with the Slovak researcher P. Koprda is the first undertaking of this kind in the Czech Republic and Slovakia.
Keywords: Literatura porównawcza; Studia porównawcze; Interdyscyplinarność; Edukacja; Czeski strukturalizm; Słowacki strukturalizm; Międzyliterackość